Level of occupational stress and its associated factors among house officers of Dow University of Health Sciences - Shahzad, Ambreen; Aijaz Ali, Saba; Urooj Fatima; Huda Erum; Munawar, Rimsha (International Journal of Endorsing Health Science Research, 2019)
Background: Work-related stress has always been an important concern in medical practice. Occupational stress and pressure in the medical profession, social expectations, training schedule, hostile job environment, and time management issues are the specific stressors in medical practice. Definite steps must be taken to overcome the effects of occupational stress. The aim of this study is to measure the level of occupational stress and its associated factors among house officers of Dow University of Health Science Ojha Campus, Karachi. Methodology: A cross-sectional study was conducted from April 2018 to July 2018, including 100 house officers from different departments including M.B.B.S., Doctor of Physiotherapy (DPT), Nursing, and Institute of Medical Technology (IMT). Informed consent was given to all those house officers who were working at the time of the study and fulfilled the inclusion criteria i.e., age 24-30 years, both male and females. Medical professionals, age >30 years, any infectious diseases were excluded. Self-designed questionnaire for demographics and workplace stress scale questionnaire based on 8 parts was used for stress evaluation and data recording. The collected data was then analyzed using SPSS 16.0 version and the ANOVA test was applied. Results: Almost equal level of stress among house officers of different departments was observed. Results were compared among different departments as mean stress level i.e. DPT *19±5.679, IMT 21.08 ± 5.627, IoN as 19.08 ± 4.890 and MBBS as 19.40 ± 4.907. According to the study results, there was no significant difference in stress level between house officers of different departments. Conclusion: Continuous or progressive stress is commonly seen among young medical professionals and is more challenging to prove their work and identity in an exhausting work environment. So, there is a need for awareness to reduce burn out and stress management strategies should be taken for improvement of mental health among young health professionals.